PENGARUH PERSEPSI POLITIK ORGANISASIONAL TERHADAP KESEHATAN MENTAL DI TEMPAT KERJA: PERAN KETRAMPILAN POLITIK DAN KEAMANAN PSIKOLOGIS - Suprapto, Yetti Lutiyan; Wahyuningsih, Tri Harsini; Sumiyarsih (Jurnal Ilmu Manajemen, 2023)
This study aims to analyze the influence of perceptions of organizational politics on mental health with political skills and psychological safety as moderating variables. The total number of respondents was 237 people, consisting of 86 lecturers and 151 education staff from various universities in Indonesia. By using SmartPLS it was found that all variables were valid and reliable, and the model was suitable for use in this research. Hypothesis testing found that perceptions of organizational politics have a positive effect on mental health. Psychological safety moderates the influence of perceptions of organizational politics on mental health, while political skills do not moderate the influence of perceptions of organizational politics on mental health. This research provides an analysis of the influence of perceptions of organizational politics not only on some mental health conditions such as stress but also on mental health conditions as a whole, and analyzes the moderation of individual internal aspects, namely political skills, and environmental aspects, namely psychological safety.